Character education during the Glory of Islam in Baghdad - Awwal, Muhammad Al; Sanur, Ilham Samudra; Ridha, M. Rasyid; Rahman, Abdul (Jurnal Edukasi Terkini, 2024)
This study covers religion and morality, which have a close and inseparable relationship, where good morality reflects the quality of a person's religiosity. In Islam, morality is considered not only an important component of religious teachings but also a basis for building a prosperous and civilised society. This study examines the relationship between religion, morality, and the success of Islamic civilisation with a focus on the contribution of the Abbasid Dynasty, especially the city of Baghdad, to the advancement of science, technology, and government administration. In addition, this study also tries to explain the role of Baghdad as a centre of global trade, culture, and education that drives the progress of the Islamic world. Heuristics, criticism, interpretation, and historiography are the four main steps in the historical research method. The purpose of this study is to show that religion and morality play an important role in building successful civilisations. With its headquarters in Baghdad, the Abbasid Dynasty made great advances in administration, science, and technology that still influence the world today. To build individuals and societies with character, good moral education is the main foundation for building an advanced and civilised civilisation. When citizens possess ethical frameworks to guide their actions and decisions, civilisations flourish. By prioritising moral education, societies can foster a sense of responsibility and community, eventually leading to greater social cohesion and progress.